National Housing Policy Implementation: Regional Aspect - Khairullina, Nursafa Gafurovna; Ustinova, Oksana Vyacheslavovna; Koltsova, Tatiana Alexsandrovna; Shvedova, Marina Fedorovna; Ivanycheva, Tatyana Alekseevna (Journal of Advanced Research in Law and Economics; Vol 6 No 3 (2015): JARLE Volume VI, Issue 3(13), Winter 2015, 2017)
Specific character of housing as an economic good of long-term use makes the problem of housing affordability extremely urgent from the point of view of customer’s purchasing power and induces the need for an efficient national housing policy. Economic reformations in Russia had a significant influence on housing prosperity of its citizens. The peculiarities of housing policy in the Soviet period and during the process of market relations becoming and development are studied in the article. The authors of the article make a conclusion that the peculiarities of the modern stage of social and economic changes in the country have caused social differentiation and polarization of the population revenues which reduced the purchasing power at the housing market. There is statistical data of providing Yamalo-Nenets Autonomous Okrug population with housing and the results of authorial sociologic research which specify problems of national housing policy at the regional level. The authors also describe measures which raise the efficiency of regional housing policy. That is increase of the population awareness by intensification of national programs informational propaganda in mass media. Another method is improvement of the reporting system of the housing programs implementation results which would also include housing program efficiency factor analysis; finding reserves for increasing the efficiency of housing programs implementation, etc.